Phylogenetic analysis and anti microbial activity of streptomyces spp. Isolated from compost soil in surabaya indonesia on the basis of 16s rrna gene - Kurnijasanti, R; Isnaeni, Isnaeni; AT, Poernomo; Sudjarwo, SA (Folia Medica Indonesiana, 2017)
Eight isolates of Streptomyces sp. can be isolated from compost soil in Surabaya, Indonesia. The results of biochemical and morphological tests showed that the 8 isolates were new. Phylogenetic analysis was performed on the sequence of 16S rRNA gene. Nucleotide sequences of 16S rRNA gene Streptomyces sp. the compost soil isolates of Surabaya were analyzed and compared with the 16S rRNA gene sequence from the literature. Streptomyces sp. the compost soil of Surabaya based on the 16S rRNA gene showed the new species of Streptomyces. The result of phylogenetic tree diagram showed that Streptomyces Sp-D, Sp-Ep, Sp-G and Sp-I found in Bratang Surabaya compost house land were new isolates. Streptomyces Sp-Ep was a new type of Streptomyces closely related to Streptomyces indonesiasis and Streptomyces nashvillensis. Streptomyces Sp-Ea was Streptomyces olivoreticuli which was still related to Streptomyces yogyakartensis. Streptomyces Sp-F was Streptomyces levis strain NRRL B-24299. Streptomyces Sp-C was Streptomyces filamentosus. Streptomyces Sp-D was a new type of Streptomyces closely related to Streptomyces javensis and Streptomyces roseus. Streptomyces Sp-G was a new type of Streptomyces closely related to Streptomyces roseoviridis strain NBRC 12911 and Streptomyces thermocarboxydovorans strain AT52. Streptomyces Sp-I was a new streptomyces that was still closely related to Streptomyces cangkringensis and Streptomyces asiaticus. Streptomyces Sp-A was Streptomyces laurentii strain: LMG 19959.